Remodeling Components of the Tumor Microenvironment to Enhance Cancer Therapy - Gkretsi, Vasiliki; Stylianou, Andreas; Papageorgis, Panagiotis; Polydorou, Christiana; Stylianopoulos, Triantafyllos (Frontiers in Oncology, 2015)
Solid tumor pathophysiology is characterized by an abnormal microenvironment that guides tumor progression and poses barriers to the efficacy of cancer therapies. Most common among tumor types are abnormalities in the structure of the tumor vasculature and stroma. Remodeling the tumor microenvironment with the aim to normalize any aberrant properties has the potential to improve therapy. In this review, we discuss structural abnormalities of the tumor microenvironment and summarize the therapeutic strategies that have been developed to normalize tumors as well as their potential to enhance therapy. Finally, we present different in vitro models that have been developed to analyze and better understand the effects of the tumor microenvironment on cancer cell behavior.